Study on the motives of Perahu Baganduang in Batik Kuansing Batik Nagori Business - Azzahra, Ridawati; Efi, Agusti (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
The Batik Perahu Baganduang motif originates from the Perahu Baganduang Tradition, a cultural practice in Kuantan Singingi Regency. Despite its growing popularity, many people are unaware of its cultural roots due to a lack of understanding. This research aims to contribute to the knowledge and appreciation of the motif, its sources of inspiration, and the symbols and meanings it carries, focusing on its application in the Kuansing Batik Nagori Batik Business. Using a qualitative approach, the research gathers primary and secondary data through observation, interviews, and documentation. The analysis follows a process of data reduction, presentation, and conclusion drawing. The findings reveal that: 1) The Batik Perahu Baganduang motif is designed to resemble the Perahu Baganduang, a boat paraded by the Lubuk Jambi community. This boat consists of two or three boats combined into one using bamboo, decorated with various colorful traditional symbols. 2) The transformation of the motif is rooted in the Perahu Baganduang Tradition itself, combined with motifs from Kuansing Batik Nagori and traditional Riau Malay designs. 3) The symbols embedded in the Batik Perahu Baganduang motif carry deep cultural significance: the Boat symbolizes unity, the Dome represents religiosity, the Buffalo Horn signifies strength, the Ani-ani symbolizes prosperity, the Gourds represent unity, the Cerano symbolizes respect, the Umbrella signifies protection, and the Colorful Cloth and Marowagh represent the indigenous community.This research provides valuable insights into the rich cultural heritage behind the Batik Perahu Baganduang motif, enhancing its appreciation and understanding within the broader community.